2017
DOI: 10.1371/journal.pone.0175728
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in association of high body mass index with early onset of Type 1 diabetes – Arab ethnicity as case study

Abstract: ObjectiveThe “accelerator hypothesis” predicts early onset of Type 1 diabetes (T1D) in heavier children. Studies testing direction of correlation between body mass index (BMI) and age at onset of T1D in different continental populations have reported differing results–inverse, direct, and neutral. Evaluating the correlation in diverse ethnic populations is required to generalize the accelerator hypothesis.MethodsThe study cohort comprised 474 Kuwaiti children of Arab ethnicity diagnosed with T1D at age 6 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…8 Ethnic variations for cut off values for BMI classes are also emphasized. 1,9 Calorie intake became twice in last 25 years according to Bangladesh National Survey. 10 Calorie intake was 1707 Kcal in 1976-77 and increased to 2344 KCal in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…8 Ethnic variations for cut off values for BMI classes are also emphasized. 1,9 Calorie intake became twice in last 25 years according to Bangladesh National Survey. 10 Calorie intake was 1707 Kcal in 1976-77 and increased to 2344 KCal in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the authors pointed to a slightly higher incidence rate in overweight, but not in obese children ( 14 ). Attempts to include additional ethnic factors showed that the accelerator hypothesis is not universal ( 15 ). Interestingly, we found that BMI-SDS was significantly higher in the older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This theory has been confirmed by some studies strongly supporting the association between BMI and earlier diagnosis of type 1 diabetes ( 6 , 9 , 10 , 11 ). Nevertheless, it is not universally accepted, as there are other studies that have contradicted these findings and do not support such a relationship ( 12 , 13 , 14 , 15 ). The starting point for the current study was a significant increase in the incidence of type 1 diabetes in the young age groups in the Lesser Poland region (from 5.2/100,000/year in 1987 to 21.9/100,000/year in 2012), which was demonstrated in our previous paper ( 16 ).…”
Section: Introductionmentioning
confidence: 90%
“…The recent study from Kuwait does indicate that ethnic differences in patient populations may explain the association between BMI and age at diagnosis. 15 In order to truly test the relevance of AH, there is a need to conduct prospective worldwide studies in ethnically diverse patient populations with a focus similar to adAPT. That will be a true tribute to a legend who sought to challenge some of the major doctrines in endocrinology during his lifetime.…”
Section: The Future Of Ahmentioning
confidence: 99%